Document Production: Visual or Logical? - Lamport, Leslie (Notices of the American Mathematical Society., 1987)
Richard Palais ran a column on mathematical typesetting in the AMS Notices, and he invited me to be guest columnist. This is what I wrote–a short exposition of my ideas about producing mathematical documents.